Correlation of Eosinophil-basophil Count and Ratio with Length of Stay in Children Dengue Infection - Yunitama, Alifa Agil Dhillu; Puspitasari, Metana; Jatmiko, Safari Wahyu; Fauziyah, Nida Faradisa (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study purpose is to determine the correlation between the number of absolute eosinophils, absolute basophils, and eosinophil-basophil ratio (EBR) with the length of stay of pediatric patients with dengue virus infection. Methodology: The study design used cross-sectional. The samples used in this study were taken from routine hematologic laboratory medical record data for the period January-October 2024, using consecutive non-probability sampling technique. Results: 49 samples were obtained and met the restriction criteria as subjects of this study. The results of the Spearman correlation bivariate test showed that the number of absolute eosinophil count, absolute basophil count, and EBR with length of stay had statistical data results respectively p = 0.139, p = 0.993, and p = 0.536. Applications/Originality/Value: This study provides a reference in laboratory results to determine the length of stay (LOS) in children with dengue virus infection.